Morfometrik, Meristik Dan Pola Pertumbuhan Ikan Toman (Channa micropeltes Cuvier, 1831) Di Waduk Plta Koto Panjang Desa Pulau Gadang Kecamatan Xii Koto Kampar Kabupaten Kampar Provinsi Riau. - Eli Yana Siregar; Ridwan Manda Putra; Eddiwan Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractToman fish (Channa micropeltes Curvier, 1831) is one type of fish that is commonly found in the Koto Panjang hydropower reservoir. This fish belongs to the Channidae family, and is the largest fish of the genus Channa. Changes in water conditions in the Koto Panjang Hydroelectric Reservoir can affect the condition of organisms in the waters. The availability of food in the waters will affect the morphometric characteristics, meristik and growth patterns of toman fish. To find out the morphometrics, meristik and growth patterns of toman fish (Channa micropeltes). This research was conducted in April-Mai 2019 toaman fish caught using fish traps and fishing rods. The measured aspects are morphometrics, meristik and length length relation of toman fish. Fish samples totaling 100 fish, consisting of 51 males and 49 females. The results of morphometric measurements are known to the total length of fish between 110-550 mm, and body weight of 18-1600 gr, its growth pattern isometric. Whereas the characteristics of the toman fish meristik are the radius of the fins respectively D.43-44.2, P.15-16, V.6-8, A.26-28.2, C.14-16. Scales on the dorsal fins 15-25, scales around the body 40-44 lines, scales on the trunk of the tail 14-18 lines, and the number of scales on the lateral line 88-95. Toman fish have ctenoid scales.Keywords: Toman fish (Channa micropeltes Curvier, 1831), Koto Panjang